Sexual activity before and after diagnosis of infection by virus of human immunodeficiency: is there any change? - Zimmermmann, Juliana Barroso; Melo, Victor Hugo; Alves, Márcio José M.; Zimmermmann, Sebastião G. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: national scope studies in the area of sexual behavior, risk and protection against infection by human immunodeficiency virus and other sexually transmitted diseases (STD) are required to formulate and evaluate public policies. Objective: the aim of this study was to evaluate whether there is change in sexual activity of patients before and after diagnosis of HIV infection. Methods: a cross-sectional study was conducted with 87 HIV seropositive patients confirmed by tests carried out previously. They were submitted to anamnesis with approach to clinical and epidemiological data. Results: the group ranged in age from 18 to 71 years. The predominant form of contagion of the human immunodeficiency virus was sexual (92%). The onset of sexual activity ranged in age from 12 to 30 years. Considering the use of condom as a mechanism of protection from STD, it was observed that 35 patients (40.2%) reported its use prior to discovery of the infection. Currently, 60 patients report some kind of protection, represented by sexual abstinence or use of condom. The comparison between these variables showed a significant association with p < 0001. Conclusion: we concluded that there is change in sexual activity of patients after diagnosis of infection with human immunodeficiency virus, represented by sexual abstinence or use of systematic condom in sex.